Scaffolding Based On Scientific Creativity Learning (SSCL): An Innovative Learning Model To Improve Student’s Skill in Scientific Creativity - Sri Astutik; Nuriman Nuriman; Supeno Supeno; Siti Maria Wardayati; Alfi Arif; Senny Weyara Dienda; Nining Ika Wahyuni; Khoirun Nisa' (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: Describe The development of the SSCL model, including validity, practicality, effectivity, and student response with the implementation of learning and student activities. This study aimed to obtain validity, practicality, effectivity, and student responses to the SSCL model in Junior high school. Method: This type of research is Research and Development (R&D) research oriented towards product development using the ADDIE development model—determination of the research location using a purposive sampling area. The sample in this study was student class VIII. Results: The results showed (1) the validity and reliability are very valid and very reliable, (2) an improved indicator of achievement with high category, (2) most of the students gave responses that scaffolding based on Scientific Creativity Learning (SSCL) models enabled them to practice scientific creativity skills in junior high school. Novelty: This research emphasizes using scaffolding for Proximal Zone Development (ZPD) approach students and students' initial conceptions of learning science. The result findings show that each phase of SSCL significantly contributes to increasing the achievement of indicators of scientific creativity.